Research on the influence of mindfulness on adolescent athlete burnout—chain mediating effect analysis of future time perspective and self-efficacy - Ouyang Yiyi; Yang Yi; Wang Kun; Luo Jiong (BMC Psychology)
Abstract Purposes This study aims to examine the relationships among mindfulness, future time perspective, self-efficacy, and athlete burnout in adolescent athletes, exploring the internal mechanisms influencing athlete burnout. It provides insights for coaches and young athletes to reduce burnout and foster healthy, confident, and optimistic lifestyles. Methods The study targeted adolescent soccer players in Chongqing, China, employing stratified random sampling for participant selection and utilizing SPSS 26.0 and AMOS 23.0 for data analysis. Results 1) Mindfulness showed a significant positive correlation with future time perspective and self-efficacy, and a significant negative correlation with athlete burnout. Future time perspective was positively correlated with self-efficacy and negatively with athlete burnout, as was self-efficacy itself; 2) Mindfulness had a direct effect (ES = -0.342) on athlete burnout. Future time perspective (ES = -0.152) and self-efficacy (ES = -0.060) each played significant mediating roles between mindfulness and athlete burnout, with the chain mediating effect of future time perspective and self-efficacy also being significant (ES = -0.051). Conclusion Mindfulness can influence adolescent athlete burnout directly as well as indirectly through the mediating effect of future time perspective and self-efficacy, and the chain mediating effect of these factors. Coaches should therefore focus on developing mindfulness in young athletes and also consider the impact of future time perspective and self-efficacy on burnout.